Ringer lactate - the magical fluid - Krishnamoorthy, Vinod H (Research and Humanities in Medical Education, 2020)
This article narrates my personal encounter with a terminally ill cancer patient at our rural clinic. I learned a lot from the experience. It made me reflect on the importance of palliative care in terminally ill patients and the practical difficulties with getting the care in rural settings. I realised that even simple interventions can be highly supportive both physically and mentally.